Morphological homeostasis in the fossil record. (April 2019) - Webster, Mark
Abstract: Morphological homeostasis limits the extent to which genetic and/or environmental variation is translated into phenotypic variation, providing generation-to-generation fitness advantage under a stabilizing selection regime. Depending on its lability, morphological homeostasis might also have a longer-term impact on evolution by restricting the variation—and thus the response to directional selection—of a trait. The fossil record offers an inviting opportunity to investigate whether and how morphological homeostasis constrained trait evolution in lineages or clades on long timescales (thousands to millions of years) that are not accessible to neontological studies. Fossils can also reveal insight into the nature of primitive developmental systems that might not be predictable from the study of modern organisms. The ability to study morphological homeostasis in fossils is strongly limited by taphonomic processes that can destroy, blur, or distort the original biological signal: genetic data are unavailable; phenotypic data can be modified by tectonic or compaction-related deformation; time-averaging limits temporal resolution; and environmental variation is hard to study and impossible to control. As a result of these processes, neither allelic sensitivity (and thus genetic canalization) nor macroenvironmental sensitivity (and thus environmental canalization) can be unambiguously assessed in the fossil record. However, homeorhesis—robustness against microenvironmental variation (developmental noise)— can be assessed in ancient developmental systems by measuring the level of fluctuating asymmetry (FA) in a nominally symmetric trait. This requires the analysis of multiple, minimally time-averaged samples of exquisite preservational quality. Studies of FA in fossils stand to make valuable contributions to our understanding of the deep-time significance of homeorhesis. Few empirical studies have been conducted to date, and future paleontological research focusing on how homeorhesis relates to evolutionary rate (including stasis), species survivorship, and purported macroevolutionary trends in evolvability would reap high reward.